Interference analysis involving HEO satellites and fixed service receivers: probabilistic modeling of the fixed service receiving antenna elevation angle - Correa Mena, A. (2014)
This paper focuses on the protection of terrestrial fixed service (FS) receivers from the aggregate interference produced by multiple highly elliptical orbit (HEO) systems operating in the 18 GHz band. Studies involving this type of interference usually consider the assumption that the victim FS receivers have their receiving antennas with zero degree elevation angle. In this work a probabilistic analysis, in which the elevation angle of the FS receiving antenna is modeled as a random variable, evaluates the aggregate interference produced by the satellites of multiple HEO systems into FS receivers. The proposed mathematical model is applied to two scenarios involving multiple interfering HEO systems and the obtained results are compared to those resulting from analyses that assume a zero degree elevation angle for the FS receiving antenna.